En torno al efecto Baldwin: evolución y lenguaje - Casas Navarro, Raymundo (2021)
By virtue of chance, a computational system defined by unbounded merge was arrived at. This specific linguistic faculty of Homo sapiens is a momentous evolutionary leap (c. 50 000 years ago) that can be explained as a genetic assimilation called Baldwin effect. In other words, in a precarious biological scenario, the best strategy is to optimize plasticity. Then, efficient learning can be funneled into the genome quickly. Although the emergence of recursive language should be explained in the evolutionary framework, there are reasonable doubts about a pure Darwinism. In order to temper skepticism, we consider that we must incorporate the mechanism known as Baldwin effect into the logical structure of the theory. To the extent that rigorous positivist methodology does not fit here, we must open up our scientific point of view. Indeed, we will resort to the heuristic power of thought experiments, potential falsifiers, and the convergence of abductive reasonings.